One-pot synthesis of VOSO4@C cathode via a versatile oxalic acid for lithium-ion batteries. (June 2021) - Zhang, Liu; Xumei Cui,; Yi, Dawei; Yang, Dingyu; Zhang, Xuefeng
Abstract: Vanadyl sulfate (VOSO4 ) Li-free cathode material was applied to lithium batteries due to the strong inductive effect of polyanions SO4 2− and vanadium-based materials exhibit excellent electrochemical activity, but their research was hindered by its extremely moisture sensitive and poor intrinsic electronic conductivities. To overcome these difficulties, we successfully synthesized carbon-coated beta-VOSO4 (β-VOSO4 @C) in one-pot synthesis method with a versatile oxalic acid as the reducing agent, carbon source and chelators, which greatly simplified the preparation process and the C layer holds back the moisture. The influence of the oxalic acid content on the microstructure and electrochemical properties of VOSO4 was studied systematically. Our studies showed that VOSO4 prepared by adding 1.3 g of oxalic acid monohydrate (VOSO@C-2) has the best performance, the amorphous carbon layer coating with a thickness of approximately 5 nm, typically reduces the electrode polarization and improves electronic conductivity. Furthermore, VOSO@C-2 delivers a maximum first discharge capacity of 163.7 mA h/g at 0.05C and a capacity retention of 70% after 110 cycles at 0.1C; furthermore, the Coulombic efficiency was retained at approximately 100%. Highlights: VOSO4 has research significance and application prospects, due to the strong induction effect of polyanion SO4 2- . One-pot synthesis of amorphous carbon coated VOSO4 with three functional roles of oxalic acid (reductants, carbon sources and chelators). The amorphous carbon layer on VOSO4 greatly prevents the moisture, HF erosion and improves electronic conductivity.